Pengaruh Kreativitas Guru terhadap Prestasi Belajar Mata Pelajaran Akidah Akhlak - Darlin Darlin; Sukman Sukman (Al-Fikr: Jurnal Pendidikan Islam, 2017)
This study discusses "The Influence of Teacher Creativity on Learning Achievement of the Subjects of Islamic Morals in Students of Class XII of Religion in Madrasa Aliyah Negeri Sorong City in 2019. The purpose of this study is to explore and describe the workings of teachers for learning XII students of religious subjects of the Islamic creed. in Madrasah Aliyah Negeri Sorong City. This type of research is quantitative research. The samples in this study were 20 people. The instrument used in this study was a questionnaire with a Likert scale. The collected data is then processed using SPSS type 22 application program assistance. Based on the results of statistical analysis with the help of the SPSS type 22 application, the results obtained at the teacher level are classified as medium qualifications, namely at intervals of 36-39. Sorong, this completes with a t count of 1.958> t table (2.080).